Adjustment outcomes of victims of cyberbullying: The role of personal and contextual factors. (October 2018) - Morin, Hillary K.; Bradshaw, Catherine P.; Kush, Joseph M.
Abstract: With many of today's youth utilizing technology to bully their peers, there is a need to better understand both predictors and consequences of cybervictimization. However, few researchers have employed a multi-level approach to jointly identify potential individual (e.g., gender) and school-level (e.g., urbanicity) predictors of cybervictimization, or examined a range of psycho-social and adjustment outcomes. The current study used survey data from 28, 583 students from 58 high schools to explore the risk factors associated with cybervictimization. We also examined the association between cybervictimization and adjustment outcomes (e.g., psychological, academic), as well as a possible moderators (e.g., student connectedness) that may buffer youth from these negative outcomes. Self-report measures assessed experiences with cybervictimization, adjustment problems, and student connectedness using previously validated measures. A series of two-level hierarchical linear modeling analyses revealed that females, underclassman, and those who are traditionally victimized or were perpetrators of cyberbullying were at significantly increased risk of cybervictimization. Cybervictimization was also associated with an increased risk of psychological (internalizing problems, sleep problems, stress problems) and academic (truancy, poor grades) adjustment problems. However, student connectedness buffered the internalizing problems experienced by victims of cyberbullying. These findings extend prior research on cybervictimization predictors, outcomes, and buffers, and in turn inform the potential use of school-based efforts aimed at preventing cyberbullying.